E-Marketplace of Muslim Food Product (EMF) / Muhamad Zarul Asyraf Ahmad Suhaimi - Ahmad Suhaimi, Muhamad Zarul Asyraf (2020)
E-Marketplace for Muslim Products (EMF) is a system or e-marketplace website where the user involve can be a buyer or a seller in this system. EMF is developed to allowed the buyer to have more exposure towards the Muslim Products and enable them to buy the products directly to the seller. By using the adapted waterfall model, the system will be developed using the sequential step by the adapted waterfall model. It has six steps which is planning, analysis, design, development, testing and documentation. Before the development of the system performed, the developer will be using several diagrams to design how the system will works. After the system has been developed, it will be tested by the four users including one-person act as the seller. Then the users will answer the questionnaire using the SUS Score question. Based on the result, the average for the total SUS Score is 70 which is above the passing line of usable system. This concludes that majority of the users are satisfy with the system that has been developed.